IECON'03. 29th Annual Conference of the IEEE Industrial Electronics Society (IEEE Cat. No.03CH37468)
DOI: 10.1109/iecon.2003.1280195
|View full text |Cite
|
Sign up to set email alerts
|

An automated fish species classification and migration monitoring system

Abstract: The quantification of abundance, distribution, and movement of fish is critical to ecological and environmental studies of fish communities. To properly manage, regulate, and protect migratory fisheries it is essential to accurately monitor numbers, size, and species of fish at specific fish passages during migratory seasons. Currently, all monitoring is done manually with significant time and financial constraints. An automated fish classirkation system will simplify data gathering and improve data accuracy.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The system has reported classification accuracy around 78%. D. J. Lee et al [22], removed edge noise and redundant data points through the development of a shape analysis algorithm. Critical landmark points were located using an algorithm of curvature function analysis.…”
Section: Related Workmentioning
confidence: 99%
“…The system has reported classification accuracy around 78%. D. J. Lee et al [22], removed edge noise and redundant data points through the development of a shape analysis algorithm. Critical landmark points were located using an algorithm of curvature function analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Cullinan et al defined four classes (bat, gull, tern, swallow), and using flight tracks reported 82% correct classification; however, this does not consider fine-grained differentiation. Lee et al (2003) used shape contour features to discriminate between nine fish species, and achieved a classification rate of between 13% and 80%. Spampinato et al (2010) also used texture and shape features, achieving a 92% correct rate.…”
Section: Studies Related To Other Speciesmentioning
confidence: 99%
“…We modified the relevance measure, K, for the curve evolution method in [28][29][30] to remove redundant points while maintaining the significance of the contours. The new relevance measure is shown in (1) where β is the turn angle on the vertex between line segments s 1 and s 2 and l(s 1 ) and l(s 2 ) are the normalized length from the vertex to the two adjacent vertices [33][34][35]. This modified curve evolution method reduces short, straight line segments that provide little information about the overall shape of the object.…”
Section: Data Point Reductionmentioning
confidence: 99%